2019
DOI: 10.1126/science.aav1937
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of van der Waals stacking–dependent interlayer magnetism

Abstract: Controlling the crystal structure is a powerful approach for manipulating the fundamental properties of solids. Unique to two-dimensional (2D) van der Waals materials, the control can be achieved by modifying the stacking order through rotation and translation between the layers. Here, we report the first observation of stacking dependent interlayer magnetism in the 2D magnetic semiconductor, chromium tribromide (CrBr 3 ), enabled by the successful growth of its monolayer and bilayer through molecular beam epi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
345
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(402 citation statements)
references
References 45 publications
35
345
1
2
Order By: Relevance
“…This picture is in agreement with recent measurements on few-layer CrI 3 where either an accidental puncture 14 or an external pressure 25,26 provided the energy to undergo a structural transformation with a corresponding transition to FM ordering. Additional validations supporting the connection between crystal structure and magnetism have been achieved in a related material, CrBr 3 , by observing different magnetic ordering associated with novel stacking patterns (not corresponding to the bulk phases) in bilayers grown by molecular beam epitaxy 27 . The ultimate confirmation of the proposed scenario requires a technique sensitive to the stacking order of few layer structures in order to verify the absence of structural phase transition in few layers.…”
mentioning
confidence: 74%
“…This picture is in agreement with recent measurements on few-layer CrI 3 where either an accidental puncture 14 or an external pressure 25,26 provided the energy to undergo a structural transformation with a corresponding transition to FM ordering. Additional validations supporting the connection between crystal structure and magnetism have been achieved in a related material, CrBr 3 , by observing different magnetic ordering associated with novel stacking patterns (not corresponding to the bulk phases) in bilayers grown by molecular beam epitaxy 27 . The ultimate confirmation of the proposed scenario requires a technique sensitive to the stacking order of few layer structures in order to verify the absence of structural phase transition in few layers.…”
mentioning
confidence: 74%
“…From an experimental perspective, direct observation of stacking-dependent interlayer magnetism in CrBr 3 has been realized successfully. 75 This study shows that while molecular beam epitaxy (MBE)-grown monolayer CrBr 3 is ferromagnetic, the interlayer coupling in its bilayer can be either ferromagnetic or antiferromagnetic depending on the exact stacking order. Figure 3A illustrates the atomic structure of Cr 2 Ge 2 Te 6 (CGT), 76 a 2D Heisenberg ferromagnet with a small out-ofplane magnetocrystalline anisotropy that results from its slightly distorted Cr-Te 6 octahedral cage with spin-orbit coupling on the Cr ions.…”
Section: Cr-based Vdw Magnetsmentioning
confidence: 99%
“…using in situ spin‐polarized scanning tunneling microscopy. [ 169 ] They found that when two single layer CrBr 3 stacked together has the same orientation, the bilayer CrBr 3 is antiferromagnetic. But when two single‐layer CrBr 3 oriented in the opposite direction(correspond to a 180° rotation between layers) are stacked together, the resulting bilayer CrBr 3 is ferromagnetic.…”
Section: Magnetism In Vdw Heterostructurementioning
confidence: 99%
“…But when two single‐layer CrBr 3 oriented in the opposite direction(correspond to a 180° rotation between layers) are stacked together, the resulting bilayer CrBr 3 is ferromagnetic. [ 169 ] Although both the detailed physics of this orientation‐dependent magnetism and the growth mechanism for specific stacking order need to be further investigated, these results demonstrate that vdW heterostructure is a promising way to manipulate magnetic properties of 2D materials.…”
Section: Magnetism In Vdw Heterostructurementioning
confidence: 99%